The inner kālacakratantra : a Buddhist tantric view of the individual - Wallace, Vesna A. (Oxford University Press, 2001)
The Kalacakratantra is the latest and most comprehensive Buddhist Tantra that is available in its original Sanskrit. The Kalacakratantra's five chapters are classified into three categories: outer, inner, and other Kalacakratantra. This text focuses on the inner Kalacakratantra.